Melt stabilization of PE with natural antioxidants: Comparison of rutin and quercetin. (June 2018) - Kirschweng, Balázs; Tilinger, Dániel Mirkó; Hégely, Bence; Samu, Gyula; Tátraaljai, Dóra; Földes, Enikő; Pukánszky, Béla
Graphical abstract: Highlights: At large amounts, rutin is as efficient stabilizer as quercetin. BDE values and interactions are not the only factors, which influence efficiency. Rutin partly decomposes under the conditions of polyethylene processing. For PE, rutin is less advantageous natural antioxidant than quercetin. Abstract: The stabilization effect of a flavonoid type natural antioxidant, rutin, was compared to that of quercetin in polyethylene. Additive concentrations changed between 0 and 500 ppm in several steps and also 1000 ppm Sandostab PEPQ phosphorus secondary stabilizer was added to each compound. Stabilization efficiency was determined by changes in vinyl group content, melt flow rate, oxygen induction time, color and the consumption of the secondary antioxidant during multiple extrusions. The results showed that rutin is as efficient melt stabilizer as quercetin used as reference. On the other hand, rutin has a deteriorating effect on the stability of the polymer at small concentrations and partially decomposes during processing. The comparison of bond dissociation enthalpies indicated that the substitution of the hydroxyl group in the ring C of quercetin by saccharide moieties increases their value, but the small increase does not influence the efficiency of the stabilizer. FTIR and DSC measurements indicated the interaction of the natural antioxidant and the phosphonite secondary stabilizer, and the development of interactions was confirmed by molecular modeling. Mainly hydrogen bonds and aromatic, π electron interactions develop between the hydroxyl groups in ring A and the POC group of the phosphonite, as well as between the aromatic rings of PEPQ and the flavonoids, but they do not influence the stabilization efficiency of the antioxidants.